(untitled) - Walton, Richard (Cambridge, UK, 2000)
Initiative is a general English course which meets the needs of more advanced learners. It is particularly suitable for students pursuing English as part of their academic studies. With its focus on reading and writing, this course is the perfect choice for teachers of large classes and groups who prefer a serious approach to language learning. The course includes: - a wide range of authentic, challenging reading texts to motivate learners at this level - clear guidance through the planning, researching and composing of written assignments, promoting learner confidence and improving students' writing skills - grammar exercises and activities which encourage students to 'rediscover' the rules of structure and usage for themselves - and remember them - extensive vocabulary work with an emphasis on collocation - optional listening and speaking activities which allow teachers greater flexibility in the classroom. Initiative is a reassuringly thorough course, extending and building on an upper intermediate level and providing a crucial first step into advanced English.
Keywords: English language,Tiếng Anh